A SECURE AND RELIABLE METHOD TO PROTECT USB DATA - Sebastian, Alycia; Sankar, K. Siva (APTIKOM Journal on Computer Science and Information Technologies, 2019)
With technology advancement people have started using different type of memory devices for storing dataand keeping it secure has become concern in today?s world. Universal Serial Bus (USB) flash drives are leadingportable storage device for storage and easy transfer of data from one computer to another. The usage of USB hasgrown exponentially and without security the data on the disk is at risk. Nowadays USB manufacturers offer passwordprotection and fingerprint authentication to secure the USB data. In this paper, USB is devised as a highly securedportable boot medium with fingerprint authentication to secure the data.